SISTEM PENUNJANG KEPUTUSAN PEMILIHAN KARYAWAN DENGAN MENGGUNAKAN ANALYTICAL HIERARCHY PROCESS - Stevan Stevan; Dedi Trisnawarman; Tri Sutrisno (Jurnal Ilmu Komputer dan Sistem Informasi, 2020)
Decision support systems are made to facilitate users in determining a decision that will be made with the help of a system. The purpose of this study is to facilitate Porence owner in selecting prospective teachers who want to apply as a teacher at Porence. Porence is a course institution engaged in English education. Data collection for this system is collected by using interviews with Porence owner. This system uses the Analytical Hierarchy Process method to determine the decisions made. This system is implemented in the form of a website so as to facilitate program accessibility by using a common browser such as Google Chrome and Mozilla Firefox. The results of the Analytical Hierarchy Process-based Decision Support system are displayed directly to the Porence owner after the data entered has met the standard method used. The results of the decision support system can be used to provide recommendations to applicants who can be accepted and who will be considered.